Endogenous borders and access to the sea. (March 2018) - Sievers, Brad; Urbatsch, R.
Abstract: A longstanding literature suggests that being landlocked inhibits countries' development. Yet a corollary implication of the underlying theories supporting this conclusion is that having multiple neighbors should lessen the drawbacks of being landlocked – and this implication does not appear to be borne out in practice. This suggests that traditional claims about the causal effect of being landlocked may be overstated. Landlocked countries instead may tend towards worse developmental outcomes because of the very same political factors – such as rough terrain, hostile neighbors, or colonial heritage – that originally led them to be cut off from the ocean. Empirical tests confirm this idea: accounting for the political factors that associate with becoming landlocked greatly reduces the estimated statistical effect of being landlocked on development. Caution is warranted when blaming lack of ocean access for social, political, and economic outcomes of interest. Highlights: Particular political and geographic factors lead to countries being landlocked. Accounting for prior conditions diminishes observed effects of being landlocked. Factors previously predicted to lessen the costs of being landlocked do not do so. Many deleterious effects attributed to being landlocked may have other causes.